the Responsibility of Professionals in Tax Crimes and Objective Imputation - Ulas, Gabriela (DIXI, 2014)
The increase in tax crimes forces us to reflct on professional conduct in the framework of criminal law. The relationship between the taxpayer and the tax authorities is generally so complex that tax advisors inevitably become involved. Th fact that certain harmless activities carried out by professionals in carrying out their work may possibly be punishable leads to an objective analysis of such conducts, leaving aside their subjective aspect. If they merely stray from their role they may become criminally responsible, regardless of the special knowledge that professionals may have outside of their work as tax advisors.
Keywords: professional conduct; tax crime; tax evasion; social role; punishable.